An analysis of IoT technology education based on UIFLOW - Varela-Aldás, José (2023)
The importance of education in new technologies today drives us to continue exploring available options to introduce students to STEAM competencies. This article presents an analysis of satisfaction in the practical education of IoT technology using a block-based programming language. In this case, the UIFlow development environment, compatible with M5Stack kits, is utilized. A graphical interface for the M5Stack Core2 AWS module's screen is designed to enable data transmission to the Thingspeak platform via the MQTT protocol with a 1-second delay. This analysis was conducted during a practical session with a group of 11 industrial engineering students. The collected data includes session runtimes and a satisfaction assessment using the Post-Study System Usability Questionnaire, specifically adapted for this case. The results indicate an overall satisfaction level of 84.7% within the group. The lowest-scoring aspect pertains to the information provided by UIFlow for problem-solving.